The power of many colours - Noga Alon; Matija Bucić; Micha Christoph; Michael Krivelevich (Forum of Mathematics, Sigma)
A classical problem, due to Gerencsér and Gyárfás from 1967, asks how large a monochromatic connected component can we guarantee in any r-edge colouring of